Induction of Escherichia coli O157:H7 into a viable but non‐culturable state by high temperature and its resuscitation. Issue 5 (6th September 2020) - Fu, Yulong; Jia, Yangyang; Fan, Jiahui; Yu, Chunna; Yu, Chungui; Shen, Chaofeng
Summary: Escherichia coli O157:H7, a causative agent of haemolytic uremic syndrome, can enter into a viable but non‐culturable (VBNC) state in response to harsh stress. Bacteria in this state can retain membrane integrity, metabolic activity and virulence expression, which may present health risks. However, virulence expression and resuscitation ability of the VBNC state are not well understood. Here, we induced E. coli O157:H7 into a VBNC state by high temperature, which is commonly used to prevent the proliferation of pathogens in process of soil solarization, composting and anaerobic digestion of organic wastes. The virulence genes were highly expressed in the VBNC state and resuscitated daughter cells. The resuscitation of VBNC cells occurred after the removal of heat stress in Luria‐Bertani medium. In addition, E. coli O157: H7 cells can leave the VBNC state and resuscitate with the clearance of protein aggregates. Notably, with the accumulation of protein aggregation and increased levels of reactive oxygen species, cells lost their ability to resuscitate. The results of this study not only can facilitate a better understanding of the health risks associated with the VBNC state but also have the potential to provide a theoretical basis for thermal disinfection processing.